Pelatihan Pendampingan Literasi Keuangan UMKM Era Digital di Majlis Taklim As Syafaah Kabupaten Sumedang Jawa Barat - Palupi, Yoppy (Jurnal Nusantara Mengabdi, 2024)
Purpose: This program aims to improve financial literacy and provide knowledge about making basic financial reports for MSMEs. Research methodology: Majlis taklim As Syafaah identifies shared needs and expectations between academic institutions, MSMEs, and Majlis Taklim. Results: Participants can do financial planning, online transaction payments, secure business capital, and make simple financial reports. Conclusions: Participants' understanding increases regarding financial planning, online transactions, simple ways to manage business capital, and preparing simple financial reports. Limitations: This research is limited to Majlis Taklim only. Contribution: Useful for participants to improve their understanding of financial literacy.